PENGGUNAAN BERBAGAI MACAM BAHAN PENGENCER TERHADAP KUALITAS SEMEN HASIL SEXING PADA KAMBING BOER - Ardhyka Chandra Stefanus; Sri Suharyati; Siswanto Siswanto; Madi Hartono (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This research aimed to determine the effect of various diluents on the quality of Boer goat’s semen after the sexing process using the BSA (Bovine Serum Albumin) albumin column method and to find out the best diluent on the quality of semen from sexing. This research was conducted on July, 11th to 25th 2019 at the Lembang Artificial Insemination Laboratory, Kayuambon, Lembang, West Java. Completely randomized design with three treatments and three replications was used in this research. The treatment given covering giving diluents of andromed (P1), skim milk (P2), and biomed (P3). The variables observed were motility, viability, and abnormality. The data were analyzed by analysis of variance (ANOVA) and it was followed by Duncan test. The results of this research indicated that the treatment using andromed (P1), skim milk (P2), and biomed (P3) was not significantly different (P>0,05) on motility, viability, and abnormality of Boer goat’s cement from sexing. Keywords : Abnormality, Boer Goat, Sexing, Motility, Viability